This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
8 1 lo g 5 3 1 + 2 7 lo g 9 3 6 + 3 lo g 7 9 4 = ( 3 4 ) ( lo g 3 5 lo g 3 3 ) 1 + ( 3 3 ) lo g 3 9 lo g 3 3 6 + 3 ( lo g 3 7 lo g 3 9 ) 4 = 3 4 × 1 lo g 3 5 + 3 3 × 2 lo g 3 3 6 + 3 2 4 lo g 3 7 = 3 4 lo g 3 5 + 3 2 3 lo g 3 3 6 + 3 2 lo g 3 7
Notice that every term in the expression is in the form of a b lo g a c
Now, let y = a b lo g a c
lo g a y = lo g a a b lo g a c lo g a y = b lo g a c lo g a a lo g a y = lo g a c b y = c b a b lo g a c = c b
We can substitute this identity into the expression:
3 4 lo g 3 5 + 3 2 3 lo g 3 3 6 + 3 2 lo g 3 7 = 5 4 + 3 6 2 3 + 7 2 = 6 2 5 + 2 1 6 + 4 9 = 8 9 0